Auto Mechanics: Technology and Expertise in Twentieth-Century America. - Kersten, Andrew E. (Journal of American History, 2008)
The article reviews the book "Auto Mechanics: Technology and Expertise in Twentieth-Century America," by Kevin L. Borg.